Thiazide-Sensitive NCC (Sodium-Chloride Cotransporter) in Human Metabolic Syndrome: Sodium Sensitivity and Potassium-Induced Natriuresis. Issue 2 (February 2021) - Preston, Richard A.; Afshartous, David; Caizapanta, Evelyn V.; Materson, Barry J.; Rodco, Rolando; Alonso, Eileen; Alonso, Alberto B.
Abstract : The thiazide-sensitive sodium-chloride cotransporter (NCC;SLC12A3) is central to sodium and blood pressure regulation. Metabolic syndrome induces NCC upregulation generating sodium-sensitive hypertension in experimental animal models. We tested the role of NCC in sodium sensitivity in hypertensive humans with metabolic syndrome. Conversely, oral potassium induces NCC downregulation producing potassium-induced natriuresis. We determined the time course and magnitude of potassium-induced natriuresis compared with the natriuresis following hydrochlorothiazide (HCTZ) as a reference standard. We studied 19 obese hypertensive humans with metabolic syndrome during 13-day inpatient confinement. We determined sodium sensitivity by change in 24-hour mean systolic pressure by automated monitor from days 5 (low sodium) to 10 (high sodium). We determined NCC activity by standard 50 mg HCTZ sensitivity test (day 11). We determined potassium-induced natriuresis following 35 mmol KCl (day 13). We determined (1) whether NCC activity was greater in sodium-sensitive versus sodium-resistant participants and correlated with sodium sensitivity and (2) time course and magnitude of potassium-induced natriuresis following 35 mmol KCl directly compared with 50 mg HCTZ. NCC activity was not greater in sodium-sensitive versus sodium-resistant humans and did not correlate with sodium sensitivity. Thirty-five-millimoles KCl produced a rapid natriuresis approximately half that of 50 mg HCTZ with a greater kaliuresis. Our investigation tested a key hypothesis regarding NCC activity in human hypertension and characterized potassium-induced natriuresis following 35 mmol KCl compared with 50 mg HCTZ. In obese hypertensive adults with metabolic syndrome ingesting a high-sodium diet, 35 mmol KCl had a net natriuretic effect approximately half that of 50 mg HCTZ. Abstract : Supplemental Digital Content is available in the text.